THE INFLUENCE OF DISCIPLINE, RESPONSIBILITY, COMMITMENT ON EMPLOYEE PERFORMANCE AT PT. ASIA COCOA - Maulana, Ervindo; Paradila Putri, Inggerit; Kusuma, Andhi; Wibisono, Chablullah (CV. Radja Publika, 2022)
The purpose of this study was to determine the effect of Discipline, Responsibility and Commitment on Employee Performance at PT. Asia Cocoa. The subjects of this study were employees of PT Asia Cocoa with the number of samples to be taken determined by the Slovin formula. The number of employees of PT Asia Cocoa is 43 people. By using the Slovin formula with a 5% margin of error, the results are obtained with a 95% presentation level. Data obtained by a questionnaire system using a Likert scale. The results of this study indicate that based on the results of the analysis in the image above, it is known that the discipline variable (X1) has a composite reliability of 0.905> 0.600, then the variable X1 is reliable, then the responsibility variable (X2) gets the composite reliability with the result 0.988> 0.600. then the variable X2 is reliable, the commitment variable (X3) gets the composite reliability results 0.877> 0.600 then the X3 variable is reliable, and the employee performance variable (Y) with the composite reliability value is 0.971> 0.600 then Y is reliable. Discipline variable (X1) produces an original sample value of 0.102 with a P value of 0.674 <0.05, so that the variable X1 has a positive and insignificant effect on variable Y employee performance. The responsibility variable (X2) produces an original sample value of 0.800 with a P value of 0.001 <0.05, so that the variable X2 has a positive and significant effect on the employee performance variable (Y). The commitment variable (X3) produces an original sample value of 0.113 with a P value of 0.179 <0.05, so that the variable X3 has a positive and insignificant effect on the employee performance variable (Y). The amount of influence of Discipline (X1).